The Implementation of School-Age Adolescent Guidance at the Nguling, Pasuruan, from the Perspective of Maqāṣid Al-Sharī'ah - Ellyanti, Nabila; Musafa'ah, Suqiyah (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
The problem of marriage dispensation that still occurs in Nguling District, Pasuruan Regency. The marriage dispensation is submitted by the couple at an early age for various reasons. Therefore, KUA at Nguling District held a school-age Adolescent Guidance (BRUS). This study aims to analyze the implementation of the School-Age Adolescent Guidance (BRUS) as an effort to emphasize the number of marriage dispensations using the perspective of maqāṣid al-sharī'ah. The method used is qualitative research with a case study approach. The data was collected through in-depth interviews with the head and religious extension workers of the KUA of Nguling District. The data was also collected through documentation. The collected data was analyzed deductively with the theory of maqāṣid al-sharī'ah. The results of the study show that the implementation of the School-Age Adolescent Guidance (BRUS) in Nguling District has been running in accordance with the provisions of the Kepdirjen Number 1012 of 2022, with the mechanism being that the implementer is the KUA of Nguling District, carried out in one working day, followed by 30 participants with a face-to-face method, and materials delivered by facilitators who have been trained. From the perspective of maqāṣid al-sharī'ah, this program has fulfilled the aspects of preserving religion, soul, intellect, heredity, and also property.